Pilipino-English-Chinese dictionary - Chen, Annie (Manila SK Pub., 1989)
Intended for foreign language students and those planning to go abroad. Entries are in Filipino, English and Fookien. Equivalent Simplified Chinese characters are also included.
Keywords: Pilipino language -- Polyglot. -- Dictionaries; Chinese language -- Polyglot. -- Dictionaries; English language -- Polyglot. -- Dictionaries